Enteroaggregative Escherichia coli heat-stable enterotoxin 1 represents another subfamily of E. coli heat-stable toxin. - Savarino, S J (1993)
Enteroaggregative Escherichia coli (EAggEC) are associated with persistent diarrhea in young children. Some of these organisms produce a low-molecular-weight, heat-stable, plasmid-encoded enterotoxin that has been named EAggEC heat-stable enterotoxin 1 (EAST1). We have cloned a 4.4-kb DNA fragment from the virulence plasmid of prototype EAggEC strain 17-2, which expresses enterotoxic activity as measured by electrogenic response in Ussing chambers mounted with rabbit ileal tissue. DNA-sequence analysis of this fragment identified an open reading frame (ORF) encoding a cysteine-rich polypeptide of 38 amino acids (M(r), 4100). Insertional and deletional mutations in this ORF resulted in loss of enterotoxic activity. The ORF was cloned into a T7 expression vector, and postinduction culture filtrates exhibited enterotoxic activity and increased ileal tissue cGMP levels. A synthetic peptide consisting of predicted amino acid residues 8-29 also showed enterotoxic activity. These data indicate that this ORF, named astA (EAggEC heat-stable enterotoxin), represents the EAST1 structural gene. EAST1 shows significant homology with the enterotoxic domain of heat-stable enterotoxin a (STa) of enterotoxigenic E. coli and with guanylin, a mammalian analog of STa. Unlike STa, which requires six cysteines and three disulfide linkages for full biological activity, both EAST1 and guanylin contain four cysteine residues. Based on the cGMP data and the sequence homology to STa and guanylin, it is predicted that EAST1 stimulates the particulate form of guanylate cyclase through the same receptor-binding region as STa and guanylin.